Russian national handball teams: gender-specific personality qualities profiling tests - Ignatyeva, V. Y.; Ovchinnikova, A. Y. (Theory and Practice of Physical Culture, 2018)
The study is the first to publish the intellectual and mental quality rates of the men`s and women`s Russian national handball teams obtained using the T. Leary Interpersonal Diagnosis of Personality Test, with a variety of personality quality rates including dominance, aggression, subordination and friendliness. The test rates were applied to find the degrees of compliance of the personality profiles with the game roles of the players. The personality profiling data of the men/ women`s Russian national handball teams varied within the range of 7-36%, with only the extreme profiles found fairly close. The study data cannot be recommended for the team composing purposes since the study was performed in the period of the poor competitive performance of both of the national teams in the top-ranking events. The handball players` personality profiling studies will be continued to find their correlations with the competitive performance rates to facilitate the team composing missions.